The use of blood protein polymorphism to estimate genetic distance among populations of Indonesian native sheep, St. Croix and Merino - Suparyanto, Agus; Purwadaria, T; ., Subandriyo; Haryati, T; Diwyanto, K (Indonesian Animal Sciences Society, 2002)
The genetic distance among populations of Indonesia native sheep (Ciamis, Garut, Sumatera and Garahan), St. Croix and Merino were estimated to investigate the genetic relationship among those breeds. Blood protein polymorphism of transferin (Tf), post-transferin (PTf), albumin (Alb), post-albumin (PAlb) were detected from blood plasma, while haemoglobine (Hb) was detected from erythrocyte using Polyacrylamide Gel Electrophoresis (PAGE). Results of PAGE showed that Tf was controlled by 6 alleles, while Alb by 4 alleles, PTf by 3 Alleles and PAlb and Hb by 2 alleles. Value of breeding coefficient within individual subpopulations (FIS) for Tf (-0,0014), Alb (-0,0046) and Hb (0,0256) were not significantly different by noel. These results show that data of gene frequency are still following Hardy-Weinberg Equilibrium and inbreeding inside the sub population did not occur. The closest distance among the native breeds is the subpopulations of Ciamis and Garut due to neighboring area and similar traits of Thin Tail Sheep. The genetic distance of both population to Sumatera Thin Tail Sheep and Garahan Fat Tail are quite far. In addition to that results all Indonesian native breed were distinctly different from St. Croix and Merino. Â Key words: Indonesian native sheep, St. Croix, Merino, blood protein polymorphism, genetic distance Â